2023
DOI: 10.3390/vaccines11040859
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Revised National Childhood Immunization Schedule on Vaccination Defaulters

Abstract: Immunization schedules affect community vaccine uptake rates, especially in children who have defaulted on their regular immunization timelines. In 2020, Singapore revised its National Childhood Immunization Schedule (NCIS) to incorporate two new combination vaccines: the hexavalent hepatitis, diphtheria, acellular pertussis, tetanus (DTaP), hemophilus influenzae b (Hib), inactivated poliovirus (IPV) (6-in-1), and the quadrivalent measles, mumps, rubella, and varicella (MMRV) vaccines, thus reducing the mean n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Addressing these factors through targeted interventions and policies is essential to improve immunization rates and ensure the health of these children. Geographical and economic factors, access to healthcare services, the grade of development of healthcare infrastructure, vaccine supply chain issues, sociocultural factors, political stability, and the government’s commitment to vaccination may modulate the impact of the COVID–19 pandemic on DTP vaccination coverage [ 49 , 50 ]. One issue to be considered is that of inequalities within countries.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing these factors through targeted interventions and policies is essential to improve immunization rates and ensure the health of these children. Geographical and economic factors, access to healthcare services, the grade of development of healthcare infrastructure, vaccine supply chain issues, sociocultural factors, political stability, and the government’s commitment to vaccination may modulate the impact of the COVID–19 pandemic on DTP vaccination coverage [ 49 , 50 ]. One issue to be considered is that of inequalities within countries.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown statistically significant differences in monthly vaccination rates between rural and urban regions [ 107 ]. The differences in vaccination trends across regions emphasize the necessity for customized public health approaches, called precision public health [ 107 , 108 ]. Policies must be region-specific, considering each area’s unique challenges and resources.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing these factors through targeted interventions and policies is essential to improve immunization rates and ensure the health of these children. Geographical and economic factors, access to healthcare services, the grade of development of healthcare infrastructure, vaccine supply chain issues, sociocultural factors, political stability, and the Government's commitment to vaccination may modulate the impact of the COVID-19 pandemic on DTP vaccination coverage [83,84]. We can observe that the countries that dropped out of the list in 2021 of those achieving WHO's DPT objectives are spread across Latin American and Caribbean regions.…”
Section: Looking To the Futurementioning
confidence: 99%

Has COVID-19 Affected DTP3 Vaccination in the Americas?

Aguinaga-Ontoso,
Guillén-Aguinaga,
Guillén-Aguinaga
et al. 2023
Preprint